(untitled) - Lišková, Štěpánka; Mandysová, Daniela (Aura musica, 2021)
The authors of this article follow and comment the development of the field of Music Education for many years, from the begin of the last education reform concretely. Glossary 3 builds on previous contributions by Dr. Lišková and is a purely current topic. From the point of view of university and high school teachers, the authors describe and evaluate the situation in the field of music during a pandemic in the past year. Based on their own experience, they point out what changes were made in the teaching of specific schools and how these changes can be projected into "ordinary" teaching positively in the future. They also deal with questions of the applications of the methods and of the forms of the work and presented topics in the distance learning.
Keywords: distance learning; Music; Glossy 3; methods and forms of work; High School; University